Erwinia chrysanthemi desensitisation in a patient with recurrent B-cell acute lymphoblastic leukemia - Çevik, Seda; Alkaya, Halil; Keser, Betül; Altaş, Uğur; Bozkurt, Hayrunnisa B.; Özkars, Mehmet Y. (Alergologia Polska - Polish Journal of Allergology, 2025)
Many hypersensitivity reactions (HSRs) are associated with chemotherapeutic agents, particularly platinum compounds, taxanes, epipodophyllotoxins, procarbazine, and L-asparaginase. For reactions to native Escherichia coli (E. coli) asparaginase, premedication, desensitization, or substitution with Erwinia chrysanthemi (ERW) or PEG-ASP (PEG-asparaginase) is preferred. Premedication and desensitization can often prevent severe reactions. A 5-year and 8-month-old male with recurrent B-cell acute lymphoblastic leukemia (B-ALL) developed an HSR during intravenous PEG-ASP infusion in the third treatment cycle. Therapy was switched to ERW, but the patient developed anaphylaxis. Due to lack of alternatives and severe previous reaction, ERW desensitization was planned. The patient received montelukast (4 mg) 36 h before, hydroxyzine (1 mg/kg), famotidine (0.5 mg/kg) 24 h before, and methylprednisolone (1 mg/kg) 12 h before the protocol. A 4-vial desensitization protocol was successfully administered every other day over 6 days without complications. HSRs to chemotherapy range from mild skin reactions to life-threatening anaphylaxis, potentially involving immunological or non-immunological mechanisms.